An EMG-control functional electrical stimulation (FES) system for restoration of gait in foot drop patients. (1st January 2013) - Sabut, S.K.; Manjunatha, M.
In this study, a non-invasive EMG-controlled Functional Electrical Stimulation (FES) system was developed and tested with normal subjects to restore foot drop during gait. To control the simulation output of the system, the subjects must retain some dorsiflexor muscle power. The control signal that adjusts the electrical stimulus intensity of ankle dorsiflexors is based on the detection of the threshold of the amplified, rectified and integrated Electromyographic (EMG) signal recorded using surface electrodes positioned over the ankle dorsiflexors and associated group of muscles. The voluntary contraction of ankle dorsiflexors could serve as the trigger of the stimulation of the system and to adjust the stimulus intensity automatically. The device was tested on a normal subject and the subject was successfully controlled the stimulus output by voluntary contracting the ankle dorsiflexion.